2023
DOI: 10.1371/journal.pone.0281893
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with pandemic management and compliance with public health measures: Evidence from a German household survey on the COVID-19 crisis

Abstract: We study how satisfaction with government efforts to respond to the COVID-19 crisis affects compliance with pandemic mitigation measures. Using a novel longitudinal household survey for Germany, we overcome the identification and endogeneity challenges involved in estimating individual compliance by using an instrumental variable approach that exploits exogenous variation in two indicators measured before the crisis: political party preferences and the mode of information measured by the frequency of using soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…On the other hand, as the light blue lines in Fig 6 indicate, an increasing share of respondents also considered measures insufficient, which may suggest higher autonomous efforts for infection prevention. While others have treated compliance in more detail [117], these findings further substantiate that significant changes occurred over time in one of the key determinants of behavioral adaptation.…”
Section: Plos Onementioning
confidence: 54%
“…On the other hand, as the light blue lines in Fig 6 indicate, an increasing share of respondents also considered measures insufficient, which may suggest higher autonomous efforts for infection prevention. While others have treated compliance in more detail [117], these findings further substantiate that significant changes occurred over time in one of the key determinants of behavioral adaptation.…”
Section: Plos Onementioning
confidence: 54%
“…On the other hand, as the light blue lines in Fig 7 indicate, an increasing share of respondents also considered measures insufficient, which may suggest higher autonomous efforts for infection prevention. While others have treated compliance in more detail [112], these findings further substantiate that significant changes occurred over time in one of the key determinants of behavioral adaptation.…”
Section: Erosion Of Trust and Compliancementioning
confidence: 54%
“…The theory of psychological reactance suggests that devaluation of policymakers may lead to noncompliance (Brehm, 1966;Díaz & Cova, 2022;Kavvouris et al, 2020;Zhang, 2020). Jaschke et al (2023) found that a one-unit increase in subjective satisfaction (on a 0-10 scale) improves protective behaviors by 2-4 percentage points.…”
Section: An Individual Perspective: the Health Belief Modelmentioning
confidence: 99%